Assessing the first Biennial Transparency Reports submitted to the UNFCCC: Are they effectively promoting transparency? - Pingault, N.; Martius, C. (CIFOR-ICRAF, 2025)
As of 27 February 2025, 105 Parties had submitted their first biennial transparency reports (BTRs) to the United Nations Framework Convention on Climate Change (UNFCCC) under the Paris Agreement – 78 when counting the European Union as a single Party. Ninety submissions, all from Non-Annex I Parties, were still pending. This paper develops a screening and scoring framework to assess transparency in this first set of BTRs, focusing on two dimensions: Data and Governance.